Anode catalyst material, and water electrolysis apparatus for hydrogen generation

JP2025020321AActive Publication Date: 2025-02-12IND TECH RES INST
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024194518
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-29
Filing Date
2024-11-06
Publication Date
2025-02-12
Estimated Expiration
2042-10-28

Smart Images

  • Figure 2025020321000001
    Figure 2025020321000001
  • Figure 2025020321000002
    Figure 2025020321000002
  • Figure 2025020321000003
    Figure 2025020321000003
Patent Text Reader

Abstract

To provide a new nonmetallic catalyst composition having both a low over-voltage and a high current activity for enhancing the activity of an oxygen evolution reaction (OER) electrode used for hydrogen generation by electrolysis, so that the new catalyst composition must realize catalytic activity and low cost at the same time.SOLUTION: An anode catalyst material has a chemical formula FeaNibMcNdOe. In the formula, M is Mo, W, Sn, Si, Nb, V, Cr, Ta, or combinations of these. a+b+c+d+e=1, a>0, b>0, c>0, d≥0, and e≥0. The anode catalyst material is able to be used for a water electrolysis apparatus for hydrogen generation. The water electrolysis apparatus includes an anode and a cathode which are arranged in an alkali aqueous solution. The anode includes the anode catalyst material.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present technical field relates to anode catalyst materials, and more particularly to water electrolysis devices for hydrogen generation using the same. [Background technology]

[0002] Due to the energy shortage, it is now urgent to find alternative sources of energy, and hydrogen energy is the best choice. Hydrogen gas used as fuel meets the requirements of environmental protection, and water electrolysis is the easiest way to produce hydrogen and oxygen. Although there are many advantages to producing hydrogen by electrolyzing water, it also has a significant drawback of consuming a lot of energy, which results in too high a cost. The excessively high energy consumption in water electrolysis is related to the excessively high overpotential, and the overpotential is related to the electrodes, electrolyte, and products of the electrochemical reaction. To increase the efficiency of water electrolysis, the electrodes are important to reduce the activation energy and increase the reaction interface, resulting in a low reaction onset potential and high current activity. The activation energy can be reduced by a catalyst on the electrode surface, which is due to the inherent catalytic properties of the electrode material.

[0003] The cathodic and anodic reactions in the process of alkaline water electrolysis are shown as follows:

[0004] The cathode reaction is: 2H2O+2e - →H2+2OH - (Hydrogen Evolution Reaction, HER)

[0005] The anode reaction is: 2OH - →H2O+1 / 2O2+2e - (Oxygen Evolution Reaction, OER)

[0006] The anode reaction is the rate-limiting step. Noble metals such as Pt or IrO2 are the best catalytic electrode materials, but they are very expensive. IrO2 needs to be replaced with another material to reduce the cost. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] U.S. Patent No. 8487733B2 [Patent Document 2] U.S. Patent No. 7468899B1 Summary of the Invention [Problem to be solved by the invention]

[0008] In order to enhance the activity of oxygen evolution reaction (OER) electrodes used to produce hydrogen by electrolysis, new non-precious metal catalyst compositions with low overpotential and high current activity are required. In addition, the new catalyst compositions must simultaneously achieve both catalytic activity and low cost. [Means for solving the problem]

[0009] One embodiment of the present disclosure is a compound having the formula Fe a Ni b M c N d O ewherein M is Mo, W, Sn, Si, Nb, V, Cr, Ta, or a combination thereof, and a+b+c+d+e=1, a>0, b>0, c>0, d≧0, and e≧0, (a) d>0 and e>0, (a1) when M is Mo, 0.0121≦a≦0.0753, 0.0366≦b≦0.2257, 0.0544≦c≦0.2917, 0.5059≦d≦0.5925, 0.0521≦e≦0.1537; (a2) when M is W, 0.0138≦a≦0.0887, 0.0417≦b≦0.2566, 0.0365≦c (a3) when M is Sn, 0.0458≦a≦0.0836, 0.1307≦b≦0.2519, 0.0440≦c≦0.1979, 0.5335≦d≦0.5853, 0.035≦e≦0.0920; (a4) when M is Si, 0.0699≦a≦0.0951, 0.2489≦b≦0.2824, 0.0136≦c≦0.0712, 0.5820≦d≦0.5983, 0.0106≦e≦0.0280; (a5) when M is Nb, (a6) when M is V, 0.0082≦a≦0.0809, 0.0277≦b≦0.2485, 0.0092≦c≦0.1524, 0.6150≦d≦0.6878, and 0.0367≦e≦0.1258; (a7) when M is Cr, 0.0057≦a≦0.0664, 0.0171≦b≦0.2055, and 0.0210≦c≦0.1694. , 0.5665≦d≦0.6904, 0.0169≦e≦0.2117;(a8) when M is Ta, 0.0710≦a≦0.0833, 0.2053≦b≦0.2432, 0.0319≦c≦0.0551, 0.5614≦d≦0.5757, 0.0410≦e≦0.0881; or (b) d=0 and e=0 or e is slightly greater than 0, (b1) when M is Mo, (b1-1) 0.0548≦a≦0.2173, 0.1367≦b≦0.6469, 0.1358≦c≦0.7815; or (b1-2) 0.(b2) when M is W, (b2-1) 0.1057 ≦ a ≦ 0.2350, 0.3211 ≦ b ≦ 0.7092, 0.0558 ≦ c ≦ 0.5732; or (b2-2) 0.3295 ≦ a ≦ 0.6485, 0.1573 ≦ b ≦ 0.2966, 0.0549 ≦ c ≦ 0.5132; (b3) when M is Sn, (b3-1) 0.1290 ≦ a ≦ 0.1832, 0.4002 ≦ b ≦ 0.5962, 0.2206 ≦ c ≦ 0.4708. or (b3-2) 0.5222≦a≦0.5647, 0.2705≦b≦0.2926, 0.1427≦c≦0.2073; (b4) when M is Si, (b4-1) 0.2080≦a≦0.2157, 0.6500≦b≦0.6895, 0.0998≦c≦0.1308; or (b4-2) 0.3457≦a≦0.6348, 0.1731≦b≦0.3318, 0.0334≦c≦0.4812.

[0010] One embodiment of the present disclosure is a water electrolysis device for hydrogen generation that includes an anode and a cathode disposed in an alkaline aqueous solution, the anode having a chemical formula of Fe a Ni b M c N d O ewherein M is Mo, W, Sn, Si, Nb, V, Cr, Ta, or a combination thereof, and a+b+c+d+e=1, a>0, b>0, c>0, d≧0, and e≧0, (a) d>0 and e>0, (a1) when M is Mo, 0.0121≦a≦0.0753, 0.0366≦b≦0.2257, 0.0544≦c≦0.2917, 0.5059≦d≦0.5925, and 0.0521≦e≦0.1537; (a2) when M is W, 0.0138≦a≦0.0887, 0.0417≦b≦0.2566, and 0.0521≦e≦0.1537; 0.0365≦c≦0.3708, 0.5035≦d≦0.5782, 0.0403≦e≦0.0778, (a3) ​​when M is Sn, 0.0458≦a≦0.0836, 0.1307≦b≦0.2519, 0.0440≦c≦0.1979, 0.5335≦d≦0.5853, 0.035≦e≦0.0920; (a4) when M is Si, 0.0699≦a≦0.0951, 0.2489≦b≦0.2824, 0.0136≦c≦0.0712, 0.5820≦d≦0.5983, 0.0106≦e≦0.0280. (a5) when M is Nb, 0.0590≦a≦0.1057, 0.2089≦b≦0.3227, 0.0052≦c≦0.1257, 0.4804≦d≦0.5454, 0.0314≦e≦0.1046; (a6) when M is V, 0.0082≦a≦0.0809, 0.0277≦b≦0.2485, 0.0092≦c≦0.1524, 0.6150≦d≦0.6878, 0.0367≦e≦0.1258; (a7) when M is Cr, 0.0057≦a≦0.0664, 0.0171≦b≦0.2055, 0 .0210≦c≦0.1694, 0.5665≦d≦0.6904, 0.0169≦e≦0.2117;(a8) when M is Ta, 0.0710≦a≦0.0833, 0.2053≦b≦0.2432, 0.0319≦c≦0.0551, 0.5614≦d≦0.5757, 0.0410≦e≦0.0881; or (b) d=0, and e=0 or e is slightly greater than 0, (b1) when M is Mo, (b1-1) 0.0548≦a≦0.2173, 0.1367≦b≦0.6469, 0.1358≦c≦0.7815; or (b1-2) 0.4979≦a≦0.6376, 0.2282≦b≦0.3188, 0.0436≦c≦0.2772; (b2) when M is W, (b2-1) 0.1057≦a≦0.2350, 0.3211≦b≦0.7092, 0.0558≦c≦0.5732; or (b2-2) 0.3295≦a≦0.6485, 0.1573≦b≦0.2966, 0.0549≦c≦0.5132; (b3) when M is Sn, (b3-1) 0.1290≦a≦0.1832, 0.4002≦b≦0.5962, 0.2206≦ c≦0.4708; or 0.1990≦a≦0.2420, 0.6566≦b≦0.7194, 0.0386≦c≦0.1444; or (b3-2) 0.5222≦a≦0.5647, 0.2705≦b≦0.2926, 0.1427≦c≦0.2073; (b4) when M is Si, (b4-1) 0.2080≦a≦0.2157, 0.6500≦b≦0.6895, 0.0998≦c≦0.1308; or (b4-2) 0.3457≦a≦0.6348, 0.1731≦b≦0.3318, 0.0334≦c≦0.4812. Effect of the Invention

[0011] The anode catalyst in some embodiments of the present disclosure can meet the requirements for producing hydrogen by electrolysis of alkaline aqueous solutions. For OER, the catalyst has high electrical conductivity and high OER electrochemical activity.

[0012] A detailed description will be given in the following embodiments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] In the following detailed description, for purposes of explanation, numerous specific details are set forth in order to provide a thorough understanding of the disclosed embodiments. However, it will be apparent that one or more embodiments may be practiced without these specific details.

[0014] One embodiment of the present disclosure is a compound having the formula Fea In b M c N d SHE ewherein M is Mo, W, Sn, Si, Nb, V, Cr, Ta, or a combination thereof, and a+b+c+d+e=1, a>0, b>0, c>0, d≧0, and e≧0. If M is another element such as Al, Zn, Y, or Sc, the material will be ineffective or less effective as an anode catalyst material. In some embodiments, (a) d>0 and e>0, and (a1) when M is Mo, 0.0121≦a≦0.0753, 0.0366≦b≦0.2257, 0.0544≦c≦0.2917, 0.5059≦d≦0.5925, and 0.0521≦e≦0.1537. In some embodiments, (a2) when M is W, 0.0138≦a≦0.0887, 0.0417≦b≦0.2566, 0.0365≦c≦0.3708, 0.5035≦d≦0.5782, and 0.0403≦e≦0.0778. In some embodiments, (a3) ​​when M is Sn, 0.0458≦a≦0.0836, 0.1307≦b≦0.2519, 0.0440≦c≦0.1979, 0.5335≦d≦0.5853, and 0.035≦e≦0.0920. In some embodiments, (a4) when M is Si, 0.0699≦a≦0.0951, 0.2489≦b≦0.2824, 0.0136≦c≦0.0712, 0.5820≦d≦0.5983, and 0.0106≦e≦0.0280. In some embodiments, (a5) when M is Nb, 0.0590≦a≦0.1057, 0.2089≦b≦0.3227, 0.0052≦c≦0.1257, 0.4804≦d≦0.5454, and 0.0314≦e≦0.1046. In some embodiments, (a6) when M is V, 0.0082≦a≦0.0809, 0.0277≦b≦0.2485, 0.0092≦c≦0.1524, 0.6150≦d≦0.6878, and 0.0367≦e≦0.1258. In some embodiments, (a7) when M is Cr, 0.0057≦a≦0.0664, 0.0171≦b≦0.2055, 0.0210≦c≦0.1694, 0.5665≦d≦0.6904, and 0.0169≦e≦0.2117.In some embodiments, (a8) when M is Ta, 0.0710≦a≦0.0833, 0.2053≦b≦0.2432, 0.0319≦c≦0.0551, 0.5614≦d≦0.5757, 0.0410≦e≦0.0881. If a, b, or c is too large or too small, the onset potential of the anode catalyst material becomes too high or the current density becomes too low during the production of hydrogen (and oxygen) by water electrolysis. If d or e is too large, the onset potential of the anode catalyst material becomes too high or the current density becomes too low during the production of hydrogen (and oxygen) by water electrolysis. If d or e is too small, the anode catalyst material becomes close to an alloy state, and the amount of nitrogen and oxygen contained in the electrocatalytic catalyst becomes too low. In this case, when hydrogen (and oxygen) is produced by water electrolysis, the Ni(OH)2 layer (which dissociates water more easily) formed on the anode catalyst layer is relatively small, resulting in a relatively high onset potential or a relatively low current density.

[0015] In some embodiments, the anode catalyst material has the formula Fe a Ni b M c N d O e where d=0 and e=0 or slightly greater than 0. In other words, the anode catalyst material is an alloy (Fe a Ni b M c ) or alloy oxide (Fe a Ni b M c O eIn some embodiments, (b1) when M is Mo, (b1-1) 0.0548≦a≦0.2173, 0.1367≦b≦0.6469, 0.1358≦c≦0.7815; or (b1-2) 0.4979≦a≦0.6376, 0.2282≦b≦0.3188, 0.0436≦c≦0.2772. In some embodiments, (b2) when M is W, (b2-1) 0.1057≦a≦0.2350, 0.3211≦b≦0.7092, 0.0558≦c≦0.5732; or (b2-2) 0.3295≦a≦0.6485, 0.1573≦b≦0.2966, and 0.0549≦c≦0.5132. In some embodiments, (b3) when M is Sn, (b3-1) 0.1290≦a≦0.1832, 0.4002≦b≦0.5962, 0.2206≦c≦0.4708; or 0.1990≦a≦0.2420, 0.6566≦b≦0.7194, 0.0386≦c≦0.1444; or (b3-2) 0.5222≦a≦0.5647, 0.2705≦b≦0.2926, 0.1427≦c≦0.2073. In some embodiments, (b4) when M is Si, (b4-1) 0.2080≦a≦0.2157, 0.6500≦b≦0.6895, 0.0998≦c≦0.1308; or (b4-2) 0.3457≦a≦0.6348, 0.1731≦b≦0.3318, 0.0334≦c≦0.4812. Similarly, if a, b, or c is too large or too small, the onset potential of the anode catalyst material is too high or the current density is too low during the production of hydrogen (and oxygen) by water electrolysis. It should be noted that the ratio of elements in the anode catalyst material can be confirmed by energy dispersive X-ray analysis (EDS). The steps of EDS are as follows: 1. SEM operating voltage is 15 kV (can be 20 kV if necessary), working distance (WD) is 8.5 mm, and EDS measuring live time is 60 to 120 seconds. 2. Before analyzing the official sample, use a copper-containing sample to collect a spectrum and correct the peaks (Cu-Ka correction).3. Qualitative analysis is performed to obtain an X-ray signal spectrum, and a more accurate qualitative analysis result is obtained from the measured elements. 4. From the qualitative analysis result, semi-quantitative analysis is performed based on the element measurement.

[0016] In some embodiments, the anode catalyst material is a continuous layer or discontinuous particles supported on the support. For example, an anode catalyst layer having a thickness of about 50 nm to 1200 nm may be formed on the support. If the thickness of the anode catalyst layer is too thin, the catalyst loading will be insufficient, resulting in a too low current density and poor catalytic activity. If the thickness of the anode catalyst layer is too thick, the stress of the anode catalyst layer applied to the support will be too high. In this case, the adhesion between the catalyst layer and the support will be insufficient. As the reaction continues, the anode catalyst will gradually dissolve and peel off from the electrode, causing a faster decay of catalytic activity. Alternatively, anode catalyst particles having a particle size of 3 nm to 25 nm may be formed on the support. If the anode catalyst particles are too small, the catalytic effect will be reduced due to macroscopic quantum tunneling effects. If the anode catalyst particles are too large, the catalytic activity will be similarly reduced due to a reduction in the surface area of ​​the catalyst. Regardless of the type, the density of the anode catalyst material on the support surface is about 0.05 mg / cm. 2 to 2 mg / cm 2 If the density of the anode catalyst material is too low, the amount of catalyst carried will be insufficient, resulting in an excessively low current density and poor catalytic activity. If the density of the anode catalyst material is too high, the stress of the anode catalyst layer applied to the support will be too high. In this case, the adhesion between the catalyst layer and the support will be insufficient, and the catalytic activity will not be enhanced or will even be reduced.

[0017] In some embodiments, the support includes a metal, a carbon material, a conductive oxide, a conductive nitride, or a combination thereof. For example, the metal can be titanium, a titanium alloy, nickel, a nickel alloy, aluminum, an aluminum alloy, another suitable metal or alloy, or a combination thereof. In some embodiments, the carbon material can be graphite, carbon nanotubes, carbon fibers, carbon microbeads, another suitable carbon material, or a combination thereof. In some embodiments, the support includes a mesh, a foam, a porous material, or a combination thereof.

[0018] One embodiment of the present disclosure provides a water electrolysis device for hydrogen generation, comprising an anode and a cathode disposed in an alkaline aqueous solution, the anode comprising an anode catalyst material. The anode catalyst material and the support for supporting the catalyst have been described above, and the relevant description will not be repeated here. In some embodiments, the alkaline aqueous solution may be NaOH, KOH, another suitable alkaline aqueous solution, or a combination thereof. In some embodiments, the pH of the alkaline aqueous solution is greater than 12 and less than or equal to 15. If the pH of the alkaline aqueous solution is too low, the conductivity of the solution will be poor. If the pH of the alkaline aqueous solution is too high, the viscosity of the solution will be too high. By applying a potential to the anode and the cathode to electrolyze the alkaline aqueous solution, the cathode can generate hydrogen and the anode can generate oxygen.

[0019] , It should be noted that the above anode catalyst can be used in the anode of multiple hydrogen generation electrolysis devices, such as membrane electrode assemblies, conventional electrolyzers, or alkaline electrolyte electrolyzers (including structural features such as liquid electrolyte and porous separators). Thus, the anode catalyst in some embodiments of the present disclosure can meet the demand for producing hydrogen by electrolysis of alkaline aqueous solutions, and the catalyst has high electrical conductivity and high electrochemical activity for the OER.

[0020] In the following, exemplary embodiments are described in detail so that those skilled in the art can easily understand the present invention. The present invention is not limited to the exemplary embodiments described herein, but may be embodied in various forms. EXAMPLES

[0021] Example 1

[0022] FeNiMoNO catalyst materials were deposited on glassy carbon (5 mmOD×4 mmH) by reactive magnetron sputtering. An FeNi3 target (available from Ultimate Materials Technology Co., Ltd.) and a Mo target (available from Ultimate Materials Technology Co., Ltd.) were prepared, and nitrogen and argon (e.g., nitrogen / (argon+nitrogen)=50%) were introduced, and reactive sputtering was performed by adjusting the sputtering power of the Mo target to obtain electrocatalytic catalyst layers of FeNiMoNO with different composition ratios (e.g., Mo / (Fe+Ni+Mo+N+O)) deposited on glassy carbon. The total flow rate of argon and nitrogen was 20 sccm, the sputtering pressure was controlled at 20 mTorr, the process temperature was controlled at room temperature, and the sputtering time was 7 to 8 minutes. The thickness of the sputtered film was about 100 nm. The composition of the FeNiMoNO catalyst material was analyzed by energy dispersive X-ray spectroscopy (EDS), and Mo / (Fe+Ni+Mo+N+O) was from 5.44at% to 29.17at%. The OER electrochemical activity of FeNiMoNO catalyst material with different composition ratios was tested. LSV measurements of oxygen evolution reaction (OER) equipment were performed in 0.1M KOH solution with Hg / HgO as the reference electrode. During the LSV measurements, the electrode was rotated at 1600rpm, the scan voltage ranged from 0.32V to 1V, the scan rate was 10mV / s, and the number of scans was 3. The electrochemical properties of the FeNiMoNO film were shown in Table 1. Mo / (Fe+Ni+Mo+N+O) achieved better OER activity from 5.44at% to 29.17at%. The best current density (mA / cm) at RHE potential of 1.878V for the catalyst was 1.01V. 2 ) is 42.99mA / cm 2 and the onset potential was 1.487V.

[0023] [Table 1]

[0024] Example 2

[0025] FeNiWNO catalyst materials were deposited on glassy carbon (5 mmOD×4 mmH) by reactive magnetron sputtering. An FeNi3 target (available from Ultimate Materials Technology Co., Ltd.) and a W target (available from Ultimate Materials Technology Co., Ltd.) were prepared, nitrogen and argon (e.g., nitrogen / (argon+nitrogen)=50%) were introduced, and reactive sputtering was performed by adjusting the sputtering power of the W target to obtain electrocatalytic catalyst layers of FeNiWNO with different composition ratios (e.g., W / (Fe+Ni+W+N+O)) deposited on glassy carbon. The total flow rate of argon and nitrogen was 20 sccm, the sputtering pressure was controlled at 20 mTorr, the process temperature was controlled at room temperature, and the sputtering time was 7 to 8 minutes. The thickness of the sputtered film was about 100 nm. The composition of FeNiWNO catalyst material was analyzed by EDS, and W / (Fe+Ni+W+N+O) was from 3.65at% to 37.08at%. The OER electrochemical activity of FeNiWNO catalyst material with different composition ratio was tested. LSV measurement of oxygen evolution reaction (OER) instrument was performed in 0.1M KOH solution with Hg / HgO as reference electrode. During LSV measurement, the electrode was rotated at 1600rpm, the scan voltage range was from 0.32V to 1V, the scan rate was 10mV / s, and the scan number was 3 times. The electrochemical properties of FeNiWNO film were shown in Table 2. W / (Fe+Ni+W+N+O) achieved better OER activity from 3.65at% to 37.08at%. The best current density (mA / cm) at RHE potential of 1.878V of catalyst was 1.01V. 2 ) is 42.56mA / cm 2 and the onset potential was 1.482V.

[0026] [Table 2]

[0027] Example 3

[0028] FeNiSnNO catalyst materials were deposited on glassy carbon (5 mmOD×4 mmH) by reactive magnetron sputtering. An FeNi3 target (available from Ultimate Materials Technology Co., Ltd.) and a Sn target (available from Ultimate Materials Technology Co., Ltd.) were prepared, nitrogen and argon (e.g., nitrogen / (argon+nitrogen)=50%) were introduced, and reactive sputtering was performed by adjusting the sputtering power of the Sn target to obtain electrocatalytic catalyst layers of FeNiSnNO with different composition ratios (e.g., Sn / (Fe+Ni+Sn+N+O)) deposited on glassy carbon. The total flow rate of argon and nitrogen was 20 sccm, the sputtering pressure was controlled at 20 mTorr, the process temperature was controlled at room temperature, and the sputtering time was 7 to 8 minutes. The thickness of the sputtered film was about 100 nm. The composition of the FeNiSnNO catalyst material was analyzed by EDS, and the Sn / (Fe+Ni+Sn+N+O) was from 4.4 at% to 23.80 at%. The OER electrochemical activity of the FeNiSnNO catalyst material with different composition ratios was tested. The LSV measurement of the oxygen evolution reaction (OER) instrument was performed in 0.1 M KOH solution with Hg / HgO as the reference electrode. During the LSV measurement, the electrode was rotated at 1600 rpm, the scan voltage ranged from 0.32 V to 1 V, the scan rate was 10 mV / s, and the number of scans was 3. The electrochemical properties of the FeNiSnNO film were shown in Table 3. The Sn / (Fe+Ni+Sn+N+O)) achieved better OER activity from 4.40 at% to 19.79 at%. The best current density (mA / cm) at RHE potential of 1.878 V of the catalyst was 1.01 V. 2 ) is 36.67mA / cm 2 and the onset potential was 1.549V.

[0029] [Table 3]

[0030] Example 4

[0031] FeNiSiNO catalyst materials were deposited on glassy carbon (5 mmOD×4 mmH) by reactive magnetron sputtering. An FeNi3 target (available from Ultimate Materials Technology Co., Ltd.) and a Si target (available from Ultimate Materials Technology Co., Ltd.) were prepared, nitrogen and argon (e.g., nitrogen / (argon+nitrogen)=50%) were introduced, and reactive sputtering was performed by adjusting the sputtering power of the Si target to obtain electrocatalytic catalyst layers of FeNiSiNO with different composition ratios (e.g., Si / (Fe+Ni+Si+N+O)) deposited on glassy carbon. The total flow rate of argon and nitrogen was 20 sccm, the sputtering pressure was controlled at 20 mTorr, the process temperature was controlled at room temperature, and the sputtering time was 7 to 8 minutes. The thickness of the sputtered film was about 100 nm. The composition of the FeNiSiNO catalyst material was analyzed by EDS, and the Si / (Fe+Ni+Si+N+O) was from 1.36 at% to 12.04 at%. The OER electrochemical activity of the FeNiSiNO catalyst material with different composition ratios was tested. The LSV measurement of the oxygen evolution reaction (OER) instrument was performed in 0.1 M KOH solution with Hg / HgO as the reference electrode. During the LSV measurement, the electrode was rotated at 1600 rpm, the scan voltage ranged from 0.32 V to 1 V, the scan rate was 10 mV / s, and the number of scans was 3. The electrochemical properties of the FeNiSiNO film were shown in Table 4. The Si / (Fe+Ni+Si+N+O) achieved better OER activity from 1.36 at% to 7.12 at%. The best current density (mA / cm) at RHE potential of 1.878 V for the catalyst was 1.01 V. 2 ) is 36.75mA / cm 2 and the onset potential was 1.545V.

[0032] [Table 4]

[0033] Example 5

[0034] FeNiNbNO catalyst materials were deposited on glassy carbon (5 mmOD×4 mmH) by reactive magnetron sputtering. An FeNi3 target (available from Ultimate Materials Technology Co., Ltd.) and a Nb target (available from Ultimate Materials Technology Co., Ltd.) were prepared, nitrogen and argon (e.g., nitrogen / (argon+nitrogen)=50%) were introduced, and reactive sputtering was performed by adjusting the sputtering power of the Nb target to obtain electrocatalytic catalyst layers of FeNiNbNO with different composition ratios (e.g., Nb / (Fe+Ni+Nb+N+O)) deposited on glassy carbon. The total flow rate of argon and nitrogen was 20 sccm, the sputtering pressure was controlled at 20 mTorr, the process temperature was controlled at room temperature, and the sputtering time was 7 to 8 minutes. The thickness of the sputtered film was about 100 nm. The composition of the FeNiNbNO catalyst material was analyzed by EDS, and the Nb / (Fe+Ni+Nb+N+O) was from 0.52 at% to 21.86 at%. The OER electrochemical activity of the FeNiNbNO catalyst material with different composition ratios was tested. The LSV measurement of the oxygen evolution reaction (OER) instrument was carried out in 0.1 M KOH solution with Hg / HgO as the reference electrode. During the LSV measurement, the electrode was rotated at 1600 rpm, the scan voltage ranged from 0.32 V to 1 V, the scan rate was 10 mV / s, and the number of scans was 3. The electrochemical properties of the FeNiNbNO film were shown in Table 5. The Nb / (Fe+Ni+Nb+N+O) achieved better OER activity from 0.52 at% to 12.57 at%. The best current density (mA / cm) at RHE potential of 1.878 V of the catalyst was 1.01 V. 2 ) is 42.55mA / cm 2 and the onset potential was 1.529V.

[0035] [Table 5]

[0036] Example 6

[0037] FeNiVNO catalyst materials were deposited on glassy carbon (5 mmOD×4 mmH) by reactive magnetron sputtering. An FeNi3 target (available from Ultimate Materials Technology Co., Ltd.) and a V target (available from Ultimate Materials Technology Co., Ltd.) were prepared, nitrogen and argon (e.g., nitrogen / (argon+nitrogen)=50%) were introduced, and reactive sputtering was performed by adjusting the sputtering power of the V target to obtain electrocatalytic catalyst layers of FeNiVNO with different composition ratios (e.g., V / (Fe+Ni+V+N+O)) deposited on glassy carbon. The total flow rate of argon and nitrogen was 20 sccm, the sputtering pressure was controlled at 20 mTorr, the process temperature was controlled at room temperature, and the sputtering time was 7 to 8 minutes. The thickness of the sputtered film was about 100 nm. The composition of FeNiVNO catalyst material was analyzed by EDS, and V / (Fe+Ni+V+N+O) was from 0.92at% to 15.24at%. The OER electrochemical activity of FeNiVNO catalyst material with different composition ratio was tested. LSV measurement of oxygen evolution reaction (OER) instrument was performed in 0.1M KOH solution with Hg / HgO as reference electrode. During LSV measurement, the electrode was rotated at 1600rpm, the scan voltage range was from 0.32V to 1V, the scan rate was 10mV / s, and the scan number was 3 times. The electrochemical properties of FeNiVNO film were shown in Table 6. The better OER activity was achieved with V / (Fe+Ni+V+N+O) from 0.92at% to 15.24at%. The best current density (mA / cm) at RHE potential of 1.878V of catalyst was obtained. 2 ) is 43.26mA / cm 2and the onset potential was 1.485V.

[0038] [Table 6]

[0039] Example 7

[0040] FeNiCrNO catalyst materials were deposited on glassy carbon (5 mmOD×4 mmH) by reactive magnetron sputtering. An FeNi3 target (available from Ultimate Materials Technology Co., Ltd.) and a Cr target (available from Ultimate Materials Technology Co., Ltd.) were prepared, nitrogen and argon (e.g., nitrogen / (argon+nitrogen)=50%) were introduced, and reactive sputtering was performed by adjusting the sputtering power of the Cr target to obtain electrocatalytic catalyst layers of FeNiCrNO with different composition ratios (e.g., Cr / (Fe+Ni+Cr+N+O)) deposited on glassy carbon. The total flow rate of argon and nitrogen was 20 sccm, the sputtering pressure was controlled at 20 mTorr, the process temperature was controlled at room temperature, and the sputtering time was 7 to 8 minutes. The thickness of the sputtered film was about 100 nm. The composition of the FeNiCrNO catalyst material was analyzed by energy dispersive X-ray spectroscopy (EDS), and the Cr / (Fe+Ni+Cr+N+O) was from 2.10 at% to 16.94 at%. The OER electrochemical activity of the FeNiCrNO catalyst material with different composition ratios was tested. The LSV measurement of the oxygen evolution reaction (OER) instrument was carried out in 0.1 M KOH solution with Hg / HgO as the reference electrode. During the LSV measurement, the electrode was rotated at 1600 rpm, the scan voltage ranged from 0.32 V to 1 V, the scan rate was 10 mV / s, and the number of scans was 3. The electrochemical properties of the FeNiCrNO film were shown in Table 7. The Cr / (Fe+Ni+Cr+N+O) achieved better OER activity from 2.10 at% to 16.94 at%. The best current density (mA / cm) at RHE potential of 1.878 V of the catalyst was obtained. 2 ) is 43.87mA / cm 2 and the onset potential was 1.478V.

[0041] [Table 7]

[0042] Example 8

[0043] FeNiTaNO catalyst materials were deposited on glassy carbon (5 mmOD×4 mmH) by reactive magnetron sputtering. An FeNi3 target (available from Ultimate Materials Technology Co., Ltd.) and a Ta target (available from Ultimate Materials Technology Co., Ltd.) were prepared, nitrogen and argon (e.g., nitrogen / (argon+nitrogen)=50%) were introduced, and reactive sputtering was performed by adjusting the sputtering power of the Ta target to obtain electrocatalytic catalyst layers of FeNiTaNO with different composition ratios (e.g., Ta / (Fe+Ni+Ta+N+O)) deposited on glassy carbon. The total flow rate of argon and nitrogen was 20 sccm, the sputtering pressure was controlled at 20 mTorr, the process temperature was controlled at room temperature, and the sputtering time was 7 to 8 minutes. The thickness of the sputtered film was about 100 nm. The composition of the FeNiTaNO catalyst material was analyzed by EDS, and the Ta / (Fe+Ni+Ta+N+O) was from 1.69 at% to 20.61 at%. The OER electrochemical activity of the FeNiTaNO catalyst material with different composition ratios was tested. The LSV measurement of the oxygen evolution reaction (OER) instrument was carried out in 0.1 M KOH solution with Hg / HgO as the reference electrode. During the LSV measurement, the electrode was rotated at 1600 rpm, the scan voltage ranged from 0.32 V to 1 V, the scan rate was 10 mV / s, and the number of scans was 3. The electrochemical properties of the FeNiTaNO film were shown in Table 8. The Ta / (Fe+Ni+Ta+N+O) achieved better OER activity from 3.19 at% to 5.51 at%. The best current density (mA / cm) at RHE potential of 1.878 V of the catalyst was 1.01 V. 2 ) is 42.12mA / cm 2 and the onset potential was 1.529V.

[0044] [Table 8]

[0045] Example 9

[0046] FeNiMo catalyst materials were deposited on glassy carbon (5mmOD×4mmH) by reactive magnetron sputtering. An FeNi3 target (available from Ultimate Materials Technology Co.,Ltd.) and a Mo target (available from Ultimate Materials Technology Co.,Ltd.) were prepared, argon was introduced, and co-sputtering was performed by adjusting the sputtering power of the Mo target to obtain electrocatalytic catalyst layers of FeNiMo with different composition ratios (e.g., Mo / (Fe+Ni+Mo)) deposited on glassy carbon. The flow rate of argon was 10sccm, the sputtering pressure was controlled at 5mTorr, the process temperature was controlled at room temperature, and the sputtering time was 3 to 4 minutes. The thickness of the sputtered film was about 100nm. The composition of the FeNiMo catalyst materials was analyzed by EDS, and the Mo / (Fe+Ni+Mo) was 13.58at% to 78.15at%. The OER electrochemical activity of FeNiMo catalyst materials with different composition ratios was tested. LSV measurements of oxygen evolution reaction (OER) equipment were carried out in 0.1 M KOH solution with Hg / HgO as the reference electrode. During the LSV measurements, the electrodes were rotated at 1600 rpm, the scan voltage ranged from 0.32 V to 1 V, the scan rate was 10 mV / s, and the number of scans was 3. The electrochemical properties of FeNiMo films were shown in Table 9. Mo / (Fe+Ni+Mo) achieved better OER activity from 13.58 at% to 78.15 at%. The best current density (mA / cm) of the catalyst at RHE potential of 1.878 V was obtained. 2 ) is 39.52mA / cm 2 and the onset potential was 1.512V.

[0047] [Table 9]

[0048] Example 10

[0049] FeNiW catalyst materials were deposited on glassy carbon (5 mmOD×4 mmH) by reactive magnetron sputtering. An FeNi3 target (available from Ultimate Materials Technology Co., Ltd.) and a W target (available from Ultimate Materials Technology Co., Ltd.) were prepared, argon was introduced, and co-sputtering was performed by adjusting the sputtering power of the W target to obtain electrocatalytic catalyst layers of FeNiW with different composition ratios (e.g., W / (Fe+Ni+W)) deposited on glassy carbon. The argon flow rate was 10 sccm, the sputtering pressure was controlled at 5 mTorr, the process temperature was controlled at room temperature, and the sputtering time was 3 to 4 minutes. The thickness of the sputtered film was about 100 nm. The composition of the FeNiW catalyst materials was analyzed by EDS, and the W / (Fe+Ni+W) was 5.58 at% to 57.32 at%. The OER electrochemical activity of the FeNiW catalyst materials with different composition ratios was tested. The LSV measurements of the oxygen evolution reaction (OER) apparatus were carried out in 0.1 M KOH solution using Hg / HgO as the reference electrode. During the LSV measurements, the electrodes were rotated at 1600 rpm, the scan voltage range was 0.32 V to 1 V, the scan rate was 10 mV / s, and the number of scans was 3. The electrochemical properties of the FeNiW films are shown in Table 10. W / (Fe+Ni+W) achieved better OER activity from 5.58 at% to 57.32 at%. The best current density (mA / cm) of the catalyst at RHE potential of 1.878 V was obtained. 2 ) is 41.21mA / cm 2 and the onset potential was 1.505V.

[0050] [Table 10]

[0051] Example 11

[0052] FeNiSn catalyst materials were deposited on glassy carbon (5 mmOD×4 mmH) by reactive magnetron sputtering. An FeNi3 target (available from Ultimate Materials Technology Co., Ltd.) and a Sn target (available from Ultimate Materials Technology Co., Ltd.) were prepared, argon was introduced, and co-sputtering was performed by adjusting the sputtering power of the Sn target to obtain electrocatalytic catalyst layers of FeNiSn with different composition ratios (e.g., Sn / (Fe+Ni+Sn)) deposited on glassy carbon. The flow rate of argon was 10 sccm, the sputtering pressure was controlled at 5 mTorr, the process temperature was controlled at room temperature, and the sputtering time was 3 to 4 minutes. The thickness of the sputtered film was about 100 nm. The composition of the FeNiSn catalyst materials was analyzed by EDS, and the Sn / (Fe+Ni+Sn) was 3.86 at% to 47.08 at%. The OER electrochemical activity of FeNiSn catalyst materials with different composition ratios was tested. LSV measurements of oxygen evolution reaction (OER) equipment were carried out in 0.1 M KOH solution with Hg / HgO as the reference electrode. During the LSV measurements, the electrodes were rotated at 1600 rpm, the scan voltage ranged from 0.32 V to 1 V, the scan rate was 10 mV / s, and the number of scans was 3. The electrochemical properties of the FeNiSn films were shown in Table 11. The better OER activity was achieved with Sn / (Fe+Ni+Sn) from 3.86 at% to 14.44 at% or from 22.06 at% to 47.08 at%. The best current density (mA / cm) at RHE potential of 1.878 V for the catalyst was 1.01 V. 2 ) is 35.12mA / cm 2 and the onset potential was 1.556V.

[0053] [Table 11]

[0054] Example 12

[0055] FeNiSi catalyst materials were deposited on glassy carbon (5mmOD×4mmH) by reactive magnetron sputtering. An FeNi3 target (available from Ultimate Materials Technology Co.,Ltd.) and a Si target (available from Ultimate Materials Technology Co.,Ltd.) were prepared, argon was introduced, and co-sputtering was performed by adjusting the sputtering power of the Si target to obtain electrocatalytic catalyst layers of FeNiSi with different composition ratios (e.g., Si / (Fe+Ni+Si)) deposited on glassy carbon. The argon flow rate was 10sccm, the sputtering pressure was controlled at 5mTorr, the process temperature was controlled at room temperature, and the sputtering time was 3 to 4 minutes. The thickness of the sputtered film was about 100nm. The composition of the FeNiSi catalyst materials was analyzed by EDS, and the Si / (Fe+Ni+Si) was 5.93at% to 32.15at%. The OER electrochemical activity of FeNiSi catalyst materials with different composition ratios was tested. LSV measurements of oxygen evolution reaction (OER) equipment were carried out in 0.1 M KOH solution with Hg / HgO as the reference electrode. During the LSV measurements, the electrodes were rotated at 1600 rpm, the scan voltage ranged from 0.32 V to 1 V, the scan rate was 10 mV / s, and the number of scans was 3. The electrochemical properties of FeNiSi films are shown in Table 12. Si / (Fe+Ni+Si) achieved better OER activity from 9.98 at% to 13.08 at%. The best current density (mA / cm) of the catalyst at RHE potential of 1.878 V was obtained. 2 ) is 33.07mA / cm 2 and the onset potential was 1.550V.

[0056] [Table 12]

[0057] Example 13

[0058] FeNiMo catalyst materials were deposited on glassy carbon (5 mmOD×4 mmH) by reactive magnetron sputtering. An Fe2Ni target (available from Ultimate Materials Technology Co., Ltd.) and a Mo target (available from Ultimate Materials Technology Co., Ltd.) were prepared, argon was introduced, and co-sputtering was performed by adjusting the sputtering power of the Mo target to obtain electrocatalytic catalyst layers of FeNiMo with different composition ratios (e.g., Mo / (Fe+Ni+Mo)) deposited on glassy carbon. The flow rate of argon was 10 sccm, the sputtering pressure was controlled at 5 mTorr, the process temperature was controlled at room temperature, and the sputtering time was 3 to 4 minutes. The thickness of the sputtered film was about 100 nm. The composition of the FeNiMo catalyst materials was analyzed by EDS, and the Mo / (Fe+Ni+Mo) was 4.36 at% to 45.98 at%. The OER electrochemical activity of FeNiMo catalyst materials with different composition ratios was tested. LSV measurements of oxygen evolution reaction (OER) equipment were carried out in 0.1 M KOH solution with Hg / HgO as the reference electrode. During the LSV measurements, the electrodes were rotated at 1600 rpm, the scan voltage ranged from 0.32 V to 1 V, the scan rate was 10 mV / s, and the number of scans was 3. The electrochemical properties of FeNiMo films were shown in Table 13. Mo / (Fe+Ni+Mo) achieved better OER activity from 4.36 at% to 27.72 at%. The best current density (mA / cm) of the catalyst at RHE potential of 1.878 V was obtained. 2 ) is 36.26mA / cm 2 and the onset potential was 1.530V.

[0059] [Table 13]

[0060] Example 14

[0061] FeNiW catalyst materials were deposited on glassy carbon (5 mmOD×4 mmH) by reactive magnetron sputtering. An Fe2Ni target (available from Ultimate Materials Technology Co., Ltd.) and a W target (available from Ultimate Materials Technology Co., Ltd.) were prepared, argon was introduced, and co-sputtering was performed by adjusting the sputtering power of the W target to obtain electrocatalytic catalyst layers of FeNiW with different composition ratios (e.g., W / (Fe+Ni+W)) deposited on glassy carbon. The flow rate of argon was 10 sccm, the sputtering pressure was controlled at 5 mTorr, the process temperature was controlled at room temperature, and the sputtering time was 3 to 4 minutes. The thickness of the sputtered film was about 100 nm. The composition of the FeNiW catalyst materials was analyzed by EDS, and the W / (Fe+Ni+W) was 1.49 at% to 51.32 at%. The OER electrochemical activity of the FeNiW catalyst materials with different composition ratios was tested. The LSV measurements of the oxygen evolution reaction (OER) apparatus were carried out in 0.1 M KOH solution using Hg / HgO as the reference electrode. During the LSV measurements, the electrodes were rotated at 1600 rpm, the scan voltage range was 0.32 V to 1 V, the scan rate was 10 mV / s, and the number of scans was 3. The electrochemical properties of the FeNiW films are shown in Table 14. W / (Fe+Ni+W) achieved better OER activity from 5.49 at% to 51.32 at%. The best current density (mA / cm) of the catalyst at RHE potential of 1.878 V was obtained. 2 ) is 34.98mA / cm 2 and the onset potential was 1.550V.

[0062] [Table 14]

[0063] Example 15

[0064] FeNiSn catalyst materials were deposited on glassy carbon (5 mmOD×4 mmH) by reactive magnetron sputtering. An Fe2Ni target (available from Ultimate Materials Technology Co., Ltd.) and a Sn target (available from Ultimate Materials Technology Co., Ltd.) were prepared, argon was introduced, and co-sputtering was performed by adjusting the sputtering power of the Sn target to obtain electrocatalytic catalyst layers of FeNiSn with different composition ratios (e.g., Sn / (Fe+Ni+Sn)) deposited on glassy carbon. The flow rate of argon was 10 sccm, the sputtering pressure was controlled at 5 mTorr, the process temperature was controlled at room temperature, and the sputtering time was 3 to 4 minutes. The thickness of the sputtered film was about 100 nm. The composition of the FeNiSn catalyst materials was analyzed by EDS, and the Sn / (Fe+Ni+Sn) was 14.27 at% to 41.39 at%. The OER electrochemical activity of FeNiSn catalyst materials with different composition ratios was tested. LSV measurements of oxygen evolution reaction (OER) equipment were carried out in 0.1 M KOH solution with Hg / HgO as the reference electrode. During the LSV measurements, the electrodes were rotated at 1600 rpm, the scan voltage ranged from 0.32 V to 1 V, the scan rate was 10 mV / s, and the number of scans was 3. The electrochemical properties of FeNiSn films are shown in Table 15. The better OER activity was achieved with Sn / (Fe+Ni+Sn) from 14.27 at% to 20.73 at%. The best current density (mA / cm) of the catalyst at RHE potential of 1.878 V was obtained. 2 ) is 32.44mA / cm 2 and the onset potential was 1.557V.

[0065] [Table 15]

[0066] Example 16

[0067] FeNiSi catalyst materials were deposited on glassy carbon (5 mmOD×4 mmH) by reactive magnetron sputtering. An Fe2Ni target (available from Ultimate Materials Technology Co., Ltd.) and a Si target (available from Ultimate Materials Technology Co., Ltd.) were prepared, argon was introduced, and co-sputtering was performed by adjusting the sputtering power of the Si target to obtain electrocatalytic catalyst layers of FeNiSi with different composition ratios (e.g., Si / (Fe+Ni+Si)) deposited on glassy carbon. The argon flow rate was 10 sccm, the sputtering pressure was controlled at 5 mTorr, the process temperature was controlled at room temperature, and the sputtering time was 3 to 4 minutes. The thickness of the sputtered film was about 100 nm. The composition of the FeNiSi catalyst materials was analyzed by EDS, and the Si / (Fe+Ni+Si) was 1.54 at% to 48.12 at%. The OER electrochemical activity of the FeNiSi catalyst materials with different composition ratios was tested. The LSV measurements of the oxygen evolution reaction (OER) device were carried out in 0.1 M KOH solution using Hg / HgO as the reference electrode. During the LSV measurements, the electrodes were rotated at 1600 rpm, the scan voltage range was 0.32 V to 1 V, the scan rate was 10 mV / s, and the number of scans was 3. The electrochemical properties of the FeNiSi films are shown in Table 16. Si / (Fe+Ni+Si) achieved better OER activity from 3.34 at% to 48.12 at%. The best current density (mA / cm) of the catalyst at RHE potential of 1.878 V was obtained. 2 ) is 36.4mA / cm 2 and the onset potential was 1.549V.

[0068] [Table 16]

[0069] Comparative Example

[0070] Pt catalyst material was deposited on glassy carbon (5 mmOD×4 mmH) by reactive magnetron sputtering. A Pt target was prepared, and argon was introduced to perform reactive sputtering to deposit a Pt layer. The flow rate of argon was 20 sccm, the sputtering pressure was controlled at 20 mTorr, the process temperature was controlled at room temperature, and the sputtering time was 5 to 6 minutes. The thickness of the sputtered film was about 100 nm. The OER electrochemical activity of Pt catalyst material and IrOx catalyst material (available from TKK) was tested, respectively. LSV measurement of oxygen evolution reaction (OER) instrument was performed in 0.1 M KOH solution with Hg / HgO as reference electrode. During LSV measurement, the electrode was rotated at 1600 rpm, the scanning voltage range was 0.32 V to 1 V, the scanning speed was 10 mV / s, and the number of scans was 3. The Pt film and IrOx catalyst material were tested for OER electrochemical activity. x The electrochemical properties of the above are shown in Table 17.

[0071] [Table 17]

[0072] It will be apparent to those skilled in the art that various modifications and variations can be made to the disclosed methods and materials. It is intended that the specification and examples be considered as exemplary only, with the true scope of the disclosure being indicated by the following claims and their equivalents.

Claims

1. Chemical formula Fe a Ni b M c N d O e wherein M is Mo, W, Sn, Si, Nb, V, Cr, Ta, or a combination thereof, a+b+c+d+e=1, a>0, b>0, c>0, d≧0, and e≧0; (a) d>0 and e>0, (a2) when M is W, 0.0138≦a≦0.0887, 0.0417≦b≦0.2566, 0.0365≦c≦0.3708, 0.5035≦d≦0.5782, and 0.0403≦e≦0.0778; (a3) when M is Sn, 0.0458≦a≦0.0836, 0.1307≦b≦0.2519, 0.0440≦c≦0.1979, 0.5335≦d≦0.5853, and 0.035≦e≦0.0920; (a4) when M is Si, 0.0699≦a≦0.0951, 0.2489≦b≦0.2824, 0.0136≦c≦0.0712, 0.5820≦d≦0.5983, and 0.0106≦e≦0.0280; (a5) when M is Nb, 0.0590≦a≦0.1057, 0.2089≦b≦0.3227, 0.0052≦c≦0.1257, 0.4804≦d≦0.5454, and 0.0314≦e≦0.1046; (a6) when M is V, 0.0082≦a≦0.0809, 0.0277≦b≦0.2485, 0.0092≦c≦0.1524, 0.6150≦d≦0.6878, and 0.0367≦e≦0.1258; (a7) when M is Cr, 0.0057≦a≦0.0664, 0.0171≦b≦0.2055, 0.0210≦c≦0.1694, 0.5665≦d≦0.6904, and 0.0169≦e≦0.2117; (a8) when M is Ta, 0.0710≦a≦0.0833, 0.2053≦b≦0.2432, 0.0319≦c≦0.0551, 0.5614≦d≦0.5757, and 0.0410≦e≦0.0881; or (b) d = 0 and e = 0 or e is slightly greater than 0; (b1) when M is Mo, (b1-1) 0.0548≦a≦0.2173, 0.1367≦b≦0.6469, 0.1358≦c≦0.7815; or (b1-2) 0.4979≦a≦0.6376, 0.2282≦b≦0.3188, 0.0436≦c≦0.2772; (b2) when M is W, (b2-1) 0.1057≦a≦0.2350, 0.3211≦b≦0.7092, and 0.0558≦c≦0.5732; (b3) when M is Sn, (b3-1) 0.1290≦a≦0.1832, 0.4002≦b≦0.5962, 0.2206≦c≦0.4708; or 0.1990≦a≦0.2420, 0.6566≦b≦0.7194, 0.0386≦c≦0.1444; or (b3-2) 0.5222≦a≦0.5647, 0.2705≦b≦0.2926, 0.1427≦c≦0.2073; (b4) when M is Si, (b4-1) 0.2080≦a≦0.2157, 0.6500≦b≦0.6895, 0.0998≦c≦0.1308; or (b4-2) 0.3457≦a≦0.6348, 0.1731≦b≦0.3318, 0.0334≦c≦0.4812, Anode catalyst materials.

2. 10. The anode catalyst material of claim 1, which is a continuous layer or discrete particles supported on a support.

3. The anode catalyst material of claim 2 , wherein the support comprises a metal, a carbon material, a conductive oxide, a conductive nitride, or a combination thereof.

4. 4. The anode catalyst material of claim 3, wherein the metal comprises titanium, a titanium alloy, nickel, a nickel alloy, aluminum, an aluminum alloy, or a combination thereof.

5. 4. The anode catalyst material of claim 3, wherein the carbon material comprises graphite, carbon nanotubes, carbon fibers, carbon microbeads, or combinations thereof.

6. The anode catalyst material of claim 3 , wherein the support comprises a mesh, a foam, a porous material, or a combination thereof.

7. A water electrolysis device for generating hydrogen, comprising an anode and a cathode disposed in an alkaline aqueous solution, The anode has the formula Fe a Ni b M c N d O e and an anode catalyst material having In the formula, M is Mo, W, Sn, Si, Nb, V, Cr, Ta or a combination thereof, and a+b+c+d+e=1, a>0, b>0, c>0, d≧0, e≧0; (a) d>0 and e>0, (a2) when M is W, 0.0138≦a≦0.0887, 0.0417≦b≦0.2566, 0.0365≦c≦0.3708, 0.5035≦d≦0.5782, and 0.0403≦e≦0.0778; (a3) when M is Sn, 0.0458≦a≦0.0836, 0.1307≦b≦0.2519, 0.0440≦c≦0.1979, 0.5335≦d≦0.5853, and 0.035≦e≦0.0920; (a4) when M is Si, 0.0699≦a≦0.0951, 0.2489≦b≦0.2824, 0.0136≦c≦0.0712, 0.5820≦d≦0.5983, and 0.0106≦e≦0.0280; (a5) when M is Nb, 0.0590≦a≦0.1057, 0.2089≦b≦0.3227, 0.0052≦c≦0.1257, 0.4804≦d≦0.5454, and 0.0314≦e≦0.1046; (a6) when M is V, 0.0082≦a≦0.0809, 0.0277≦b≦0.2485, 0.0092≦c≦0.1524, 0.6150≦d≦0.6878, and 0.0367≦e≦0.1258; (a7) when M is Cr, 0.0057≦a≦0.0664, 0.0171≦b≦0.2055, 0.0210≦c≦0.1694, 0.5665≦d≦0.6904, and 0.0169≦e≦0.2117; (a8) when M is Ta, 0.0710≦a≦0.0833, 0.2053≦b≦0.2432, 0.0319≦c≦0.0551, 0.5614≦d≦0.5757, and 0.0410≦e≦0.0881; or (b) d = 0 and e = 0 or e is slightly greater than 0; (b1) when M is Mo, (b1-1) 0.0548≦a≦0.2173, 0.1367≦b≦0.6469, 0.1358≦c≦0.7815; or (b1-2) 0.4979≦a≦0.6376, 0.2282≦b≦0.3188, 0.0436≦c≦0.2772; (b2) when M is W, (b2-1) 0.1057≦a≦0.2350, 0.3211≦b≦0.7092, and 0.0558≦c≦0.5732; (b3) when M is Sn, (b3-1) 0.1290≦a≦0.1832, 0.4002≦b≦0.5962, 0.2206≦c≦0.4708; or 0.1990≦a≦0.2420, 0.6566≦b≦0.7194, 0.0386≦c≦0.1444; or (b3-2) 0.5222≦a≦0.5647, 0.2705≦b≦0.2926, 0.1427≦c≦0.2073; (b4) when M is Si, (b4-1) 0.2080≦a≦0.2157, 0.6500≦b≦0.6895, 0.0998≦c≦0.1308; or (b4-2) 0.3457≦a≦0.6348, 0.1731≦b≦0.3318, 0.0334≦c≦0.4812, A water electrolysis device used to generate hydrogen.

8. 8. The water electrolysis device used for generating hydrogen according to claim 7, wherein the pH of the alkaline aqueous solution is greater than 12 and less than or equal to 15.

Citation Information

Patent Citations

  • Iron-doped transition metal-based oxide electrode material and preparation method and application thereof

    CN113718285A

  • Ti anode electrode member for producing electrolytic manganese dioxide

    JP1994299388A

  • Alloy lump and its production

    JP1996104929A

  • Manufacturing method of powder sintered body containing nitrogen

    JP2012201962A

  • Electrode for alkaline water electrolysis, method for manufacturing the same and hydrogen generator

    JP2018127664A